Antibodies titer of dogs immunized by anti-idiotypic vaccine detected by using enzyme linked immunosorbent assay - Sayu Putu Yuni Paryati; Retno D. Soejoedono; Eka Noneng Nawangsih (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Rabies control programs, including extensive vaccination with attenuated or inactivated vaccines. However, such vaccines are not without problems and can have detrimental effects. Indeed attenuated vaccines can revert to a more virulent form, and inactivated vaccines may produce serious side effects. These facts, have led to the creation of a new generation of vaccines: recombinant-DNA vaccines, synthetic peptide vaccines, and anti-idiotypic vaccines. The aim of this study is to study the result of anti-idiotypic immunization methods in dogs detected by using enzyme linked immunosorbent assay (ELISA). Anti-idiotype antibodies against rabies (Ab2) were isolated from chicken blood, separated by means of ammonium sulfate precipitation, then dialyzed using PBS pH 8.0 for 24 hours at 2 – 8 oC and purified using affinity chromatography column. Three groups of dogs were immunized, group I was immunized intramuscularly (i.m) with purified IgY, group II was immunizded oraly (p.o) with purified IgY and group III was immunized intramuscularly (i.m) with rabies viral vaccines.  The antibody response (Ab3) was detected using Agar Gel Precipitation Test (AGPT). The efficacy of Ab3 was detected using ELISA. By ELISA, the result of immunization indicated that the level of Ab3 titers of anti-idiotypic vaccine immunized dogs intramuscularly are more than 0.5 IU/ml (protective according to WHO standard), and significantly higher than oraly immunization, but it significantly lower than Ab3 titers of rabies viral vaccine immunized dogs. The conclusion of this study is intramuscularly immunization of anti-idiotypic antibodies can induce protective immune response against rabies virus, although its lower than antibodies titer of viral vaccine, it has a good prospect for vaccine development in controlling rabies